2020
DOI: 10.1021/acs.inorgchem.9b03183
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of MAPbBr3Perovskite Quantum Dots on Perovskite MOFs by a One-Step Mechanochemical Synthesis

Abstract: We report a one-step, solvent-free, green approach for the mechanochemical stabilization of hybrid organic–inorganic lead halide (MAPbBr3) perovskite quantum dots (PQDs) within perovskite metal–organic frameworks (MOFs) [MA-M­(HCOO)3] [M = Mn and Co; MA = methylammonium (CH3NH3 +)]. The perovskite MOF acts as a template and source of MA cations for growing and stabilizing hybrid PQDs. The synthesis of the composite has been carried out mechanochemically, without the use of any external reagents by simply grin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 54 publications
(26 reference statements)
0
50
0
Order By: Relevance
“…The 2D perovskite can be formed by alternating A and [B 2 X 5 ] À layers for AB 2 X 5 [25] or alternating [BX 6 ] 4À octahedras and large cation A for A 2 BX 4 or A 3 B 2 X 9 . [26,27] Generally, the 2D perovskite family is built upon the chemical slicing of 3D perovskite along (100), (110) and (111) crystal planes, yielding A 0 2 A n-1 B n X 3nþ1 , A 0 2 A m B m X 3mþ2 , and A 0 2 A q-1 B q X 3qþ3 , respectively. [28] The 3D perovskite also includes the A 2 B þ B 03þ X 6 -type structure, which is called double perovskite, [29] and the corresponding layered 2D perovskites.…”
Section: Perovskite Semiconductors: Structure and Dimensionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 2D perovskite can be formed by alternating A and [B 2 X 5 ] À layers for AB 2 X 5 [25] or alternating [BX 6 ] 4À octahedras and large cation A for A 2 BX 4 or A 3 B 2 X 9 . [26,27] Generally, the 2D perovskite family is built upon the chemical slicing of 3D perovskite along (100), (110) and (111) crystal planes, yielding A 0 2 A n-1 B n X 3nþ1 , A 0 2 A m B m X 3mþ2 , and A 0 2 A q-1 B q X 3qþ3 , respectively. [28] The 3D perovskite also includes the A 2 B þ B 03þ X 6 -type structure, which is called double perovskite, [29] and the corresponding layered 2D perovskites.…”
Section: Perovskite Semiconductors: Structure and Dimensionmentioning
confidence: 99%
“…[46,[48][49][50] The epitaxial growth of perovskite MAPbBr 3 NCs on MoS 2 was also achieved by a solution route. [51] The heterojunctions showed that the perovskite epitaxial relationship within (001) MoS 2 nanosheets aligned along either the MAPbBr 3 [100]/MoS 2 [100] direction or the MAPbBr 3 [110]/MoS 2 [210] direction.…”
Section: Epitaxial Growth Of Van Der Waals Heterojunctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[65] Thes ame group later reported grinding aC H 3 NH 3 -containing MOF with PbBr 2 to generate aperovskite-MOF composite. [66] The progress suggests the potential of mechanochemistry for perovskite-MOF composites,a lthough more work is needed to routinely realize one-pot synthesis in this manner.…”
Section: One-pot Synthesismentioning
confidence: 99%
“…Smart integration of MOFs with perovskites has been proven to control the agglomeration allows excellent features like high thermal stability, significant water resistance stable photoluminescence, excellent charge separation efficiency, and important gas capturing/activation ability. [ 66–73 ] Recently, a few strategies have been reported for synthesizing hybrid MOFs by encapsulating various perovskite halides (hybrids denoted as MHP@MOF), allowing optoelectronic and energy harvesting applications. This review offers a broad overview of the state‐of‐the‐art in MHP@MOF hybrids synthesis, along with the challenges, opportunities, and future perspectives.…”
Section: Introductionmentioning
confidence: 99%